Effect of Feeding Green Azolla (Azolla pinnata) on Growth Performance in Sirohi Male Kids - Sharma, Naveen Kumar; Joshi, Monika; Sharma, Shiv Kumar (International Journal of Livestock Research, 2021)
The aim of this study was to determine the effect of feeding green Azolla (Azolla pinnata) on growth performance in Sirohi male kids. A feeding trial of ninety days was conducted on 16 Sirohi male kids of 4-6 months of age. The experimental kids were distributed randomly in four treatment groups viz. T1 - Control (Basal roughage + concentrate); T2 (Basal roughage + concentrate + 150gm green Azolla); T3 (Basal roughage + concentrate + 250 gm green Azolla); and T4 (Basal roughage + concentrate + 350 gm green Azolla). There was highly significant (P<0.01) effect of green Azolla (Azolla pinnata) feeding on periodical body weight change, average daily gain and feed conversion ratio in different treatments and periods. It was concluded that green Azolla (Azolla pinnata) improved the growth performance of Sirohi kids when fed @ 250gm along with concentrate diet.